2018
DOI: 10.3390/ijms19123945
|View full text |Cite
|
Sign up to set email alerts
|

The Cytomegalovirus-Specific IL-21 ELISpot Correlates with Allograft Function of Kidney Transplant Recipients

Abstract: In kidney transplant recipients, the cytomegalovirus (CMV) is frequently causing infection/reactivation and can trigger allograft rejection. To assess the risk of reactivation, the cellular immune response against CMV is increasingly assessed by cellular in vitro methods, such as the interferon (IFN)-γ ELISpot. In the current study we compared the IFN-γ ELISpot with our newly established CMV-specific ELISpot assays determining IL-17A, IL-21, IL-22, granzyme B, and perforin and correlated the results with flow … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(35 citation statements)
references
References 38 publications
4
31
0
Order By: Relevance
“…36 In transplantation, several complications are associated with sex, including acute rejection, graft loss and viral (re)activations. 11,13,37,38 However, the underlying reasons for these sex differences are not well understood; possible causes include the hormonal regulation of the immune system, the effects of pregnancy, and differences in the metabolism of drugs routinely employed in transplantation. 11 For example, there is tentative evidence of sexrelated differences in the pharmacokinetics of (val)ganciclovir.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…36 In transplantation, several complications are associated with sex, including acute rejection, graft loss and viral (re)activations. 11,13,37,38 However, the underlying reasons for these sex differences are not well understood; possible causes include the hormonal regulation of the immune system, the effects of pregnancy, and differences in the metabolism of drugs routinely employed in transplantation. 11 For example, there is tentative evidence of sexrelated differences in the pharmacokinetics of (val)ganciclovir.…”
Section: Discussionmentioning
confidence: 99%
“…11,12 Furthermore, it has been shown repeatedly that women and men have different anti-CMV immunological profiles, with an impact in the graft function and even the phenotype of the immune system as a whole. 13,14,18 Notably, in a recent publication, Lindemann et al have observed an association of high numbers of IL-21-secreting anti-CMV T cells with female sex and lower eGFR in a clinical transplantation context. 13 Our analyses may provide some evidence on the nature of the observed association of eGFR-1y with prevention strategies in female patients.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations